EURASIAN CLINICAL GUIDELINES ON DIAGNOSIS AND TREATMENT OF ACUTE CORONARY SYNDROME WITH ST SEGMENT ELEVATION (STEMI) - I. I. Staroverov; R. M. Shakhnovich; M. Yu. Gilyarov; A. L. Komarov; E. V. Konstantinova; E. P. Panchenko; I. S. Yavelov (Евразийский Кардиологический Журнал)
.